Alleles of major histocompatibility complex BoLA class II associated with resistance and susceptibility to Boophilus microplus in cattle, Junín, Peru - Villanueva M., Custodio (2011)
The aim of this study was identified by amplification of microsatellite alleles of the Major Histocompatibility Complex BoLA Class II associated with resistance and susceptibility to Boophilus microplus in cattle, Junín, Peru. We collected blood sample of 47 cattle, as well as specimens of B. microplus during the months of march, april and may 2009 in the morning, the right side of each animal. Genomic DNA extraction was performed by the method of Phil Summers (1995) and amplification of microsatellites DRB3.2, DRB31 and BM1815 was by PCR in an automatic sequencer. Data were evaluated using the program POPG 32. We identified alleles A, B and C related to resistance and susceptibility to B. microplus in cattle both in the BoLA locus BoLA DRB3.2 as BM1815. Allele frequencies were estimated: the DRB3.2 locus allele frequency was 0.2742, allele B was 0.5000 and the C allele was 0.2258, in the DRB31 locus allele frequency was 1.0000 and at the BM1815 locus allele frequency was 0.3295, allele B was 0.5909y the C allele was 0.0795. We conclude that the alleles A, B and C loci BM1815 DRB3.2 and Major Histocompatibility Complex Class II BoLA are associated with resistance to B. microplus in cattle and DRB31 locus allele is associated with susceptibility.